Perencanaan Pembangunan Instalasi Pengolahan Lumpur Tinja (IPLT) Di Kecamatan Tampan Kota Pekanbaru - Hidayat, Hafizhul; Sasmita, Aryo; Reza, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Tampan District doesn’t have a facility construction faecal sludge treatment plan so that the septic tank draining directly discharges to open lands. Based on Permen PU No. 01/PRT/M/2014 Tampan District already complete the minimum services standards of a faecal sludge treatment plan was planned to solve the faecal sludge problem in four subdistrict in Tampan District. Processing system that is applied is physically processing by sludge seperation chamber (SSC) to separate solids from faecal sludge at the beginning of processing, SSC are provided 4 bath processing efficiency for BOD 35% and TSS 85%. Subsequent processing in biology by the 2 units of anaerobic baffle reactor (ABR) each of which consists of five compartments, 2 units ABR processing efficiency for BOD 95% and 85%, TSS is 85% and 80%. the Characteristics of faecal sludge before processing BOD 6,400 mg/l and TSS 29,900 mg/l. t Effluents water from the faecal sludge processing already met the standard based on Permen LH No. 5 in 2014 with a value of BOD 36 mg / liter and the value of TSS 155 mg / liter.Keywords: Subdistrict Tampan, Faecal Sludge, IPLT, Sludge Separation Chamber (SSC), Anaerobic Baffle Reactor (ABR).